PLAIE ACCIDENTELLE DE L’ARTERE RADIALE LORS DE L’ABORD ANTERIEUR DE L’AVANTBRAS : INTERET DU NON USAGE DU GARROT - Walla, Atchi; James, EdèmYaovi; Gnandi-Pio, Faré; Ayouba, Gamal; Darré, Tchin; Abalo, Anani; Dossim, Assang Michel (European Scientific Journal, ESJ, 2015)
Authors report one case of radial artery accidental wound in a 37 years old man who has presented malunion at the one third middle of the two forearm bones during radial focal abord by Henry way. The external bord of flexor carpi radialis muscle was not easy to identify because of anatomics connections modifications by malunion itself and amyotrophy. The garrot was not used at the beginning. A longitudinal wound of about one half centimeter of radial artery occurred and was repaired by classic way. Postoperative affects were simples. The tourniquet non use permit to recognize immediately the complication and to treat it quickly.